From Vitality to Security: Stem Cells and Testosterone Supporting Health and National Defense with the Vinski Protocol - Deby Susanti Pada Vinski Vinski; Natasha Cinta Vinski; Svetlana Trofimova; Andi Kurniawan Nugroho; Prihati Pujowaskito (Journal of World Science, 2025)
The vitality and health of a nation’s citizens, especially its emergency and defense forces, are inseparable from national security. Regenerative and hormonal medicine is an exciting new field in performance medicine. This Phase 1 clinical trial assesses the safety and initial effectiveness of the Vinski Protocol, an innovative therapy involving umbilical cord-derived mesenchymal stem cells (UC-MSCs) in conjunction with testosterone optimization therapy. Twenty-five healthy men, aged 25-45 years, received three intravenous infusions of UC-MSCs and weekly testosterone cypionate for 12 weeks. Primary outcomes measured safety through adverse event monitoring and clinical laboratory profiles, and secondary outcomes were serum testosterone change, VO2 max, body composition, inflammatory markers (C-reactive protein [CRP] and interleukin 6 [IL-6]), and subjective vitality. The protocol was well-tolerated with no serious adverse events; 12% of subjects reported mild fatigue. Statistically significant changes were noted in testosterone level (+215 ng/dL, p < 0.01), lean mass (+2.1 kg, p < 0.05), VO2 max (+11.8%, p < 0.05), and decreases in CRP and IL-6 (p < 0.05). Energy and mental clarity also improved in subjects. These findings provide evidence for the feasibility and potential effectiveness of the Vinski Protocol as a dual regenerative-hormonal approach to increasing individual vitality and overall health resilience.